2005
DOI: 10.1088/1478-3975/2/2/s03
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interactions: organization, cooperativity and mapping in a bottom-up Systems Biology approach

Abstract: Understanding and ultimately predicting protein associations is immensely important for functional genomics and drug design. Here, we propose that binding sites have preferred organizations. First, the hot spots cluster within densely packed 'hot regions'. Within these regions, they form networks of interactions. Thus, hot spots located within a hot region contribute cooperatively to the stability of the complex. However, the contributions of separate, independent hot regions are additive. Moreover, hot spots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 105 publications
1
84
0
Order By: Relevance
“…From this result, we confirmed that, out of 238 binding residues in all 17 mutant structures, 2 binding residues having identical flexibility, 39 binding residues having increased flexibility, and 197 binding residues having decreased flexibility. This result could clearly exemplified that decreased flexibility in the binding residues of 17 mutant structures of ADD domain changed the conformational state of interfacial residues and could affect the evolutionary molecular recognition of histone H3-peptide according to ''conformational selection'' method (Keskin et al 2005). Interestingly, two variants L192F and Q219P had more pronounced effect on ADD domain by computational tools (I-Mutant 2.0, SIFT, PolyPhen) and structure-based methods (total energy, RMSD, inter-intra molecular interactions, Rosetta energy score and normal mode analysis) leads to cause ATR-X syndrome.…”
Section: Computing Intra-molecular Interactions In Add Domain Of Atrxmentioning
confidence: 97%
“…From this result, we confirmed that, out of 238 binding residues in all 17 mutant structures, 2 binding residues having identical flexibility, 39 binding residues having increased flexibility, and 197 binding residues having decreased flexibility. This result could clearly exemplified that decreased flexibility in the binding residues of 17 mutant structures of ADD domain changed the conformational state of interfacial residues and could affect the evolutionary molecular recognition of histone H3-peptide according to ''conformational selection'' method (Keskin et al 2005). Interestingly, two variants L192F and Q219P had more pronounced effect on ADD domain by computational tools (I-Mutant 2.0, SIFT, PolyPhen) and structure-based methods (total energy, RMSD, inter-intra molecular interactions, Rosetta energy score and normal mode analysis) leads to cause ATR-X syndrome.…”
Section: Computing Intra-molecular Interactions In Add Domain Of Atrxmentioning
confidence: 97%
“…All this will favour the establishment of strong enthalpic contributions, but these would not have a significant impact on the binding energetics if they were coupled to structuring effects in highly flexible regions of the protein. Interestingly, hot spots are generally well structured and preferably found in preexisting pockets in the free protein that are not affected by ligand induced conformational changes [161][162][163]. It could be argued that, among other factors, the high structural stability of these residues is, thus, determinant for their strong contribution to the binding energy.…”
Section: The Structural Stability Of Binding Sitesmentioning
confidence: 99%
“…Identifying protein binding sites and knowing which proteins interact with which others are crucial for a better understanding of the bases of many biological processes. Despite the ongoing effort to decipher the complex nature of protein interactions, they are not still entirely understood (1)(2)(3)(4)(5). Protein binding sites have been thoroughly analyzed for the presence of certain physico-chemical and geometric properties that can be used to distinguish these regions from the non-interacting surface regions.…”
Section: Introductionmentioning
confidence: 99%